Effect of etanercept therapy on psoriasis symptoms in patients from Latin America, Central Europe, and Asia: A subset analysis of the PRISTINE trial - L. Kemeny (2018)
© 2015 Kemeny et al. Background: Psoriasis prevalence and characteristics in Asia, Central Europe, and Latin America have not been thoroughly investigated and there are no large trials for biologic treatments for patients from these regions. The goal of this analysis was to report clinical response to anti-tumor necrosis factor-alpha treatment in these patients. Methods: Patients from Argentina, Czech Republic, Hungary, Mexico, Taiwan, and Thailand (N = 171) were included in this subset analysis of the PRISTINE trial. Patients with stable moderate-to-severe plaque psoriasis were blinded and randomized to receive etanercept 50 mg once weekly (QW) or biweekly (BIW) for 12 weeks, followed by 12 weeks of open-label QW treatment with etanercept 50 mg through week 24 (QW/QW vs. BIW/QW). Concomitant methotrexate (≤20 mg/week) and mild topical corticosteroids or other agents were permitted at the physician's discretion, in accordance with therapeutic practice. Results: As early as week 8, 26.7 % in the etanercept QW group and 44.0 % in the BIW group achieved Psoriasis Area and Severity Index (PASI) 75. At weeks 12 and 24, respectively, PASI 75 increased to 39.5 % and 62.8 % in the QW/QW group and 66.7 % and 83.3 % in the BIW/QW group. PASI 75 was significantly different between treatment groups from week 8 through the end of study (p < 0.05). The Kaplan-Meier estimate of the proportions achieving PASI 75 in QW/QW and BIW/QW groups, respectively, was 27.4 % and 45.8 % through week 8; 41.9 % and 68.7 % through week 12; and 72.5 % and 95.2 % through week 24. Conclusions: Treatment with etanercept 50 mg provided rapid relief of psoriasis symptoms in patients from Asia, Central Europe, and Latin America. A more rapid response was observed in patients who received BIW treatment for the first 12 weeks which was sustained after reducing to QW dosing for the subsequent 12 weeks. Response rates were similar to those observed in the overall PRISTINE population. Trial registration: ClinicalTrials.gov identifier NCT00663052